Pengaruh Kinerja dan Ukuran Perusahaan Terhadap Stock Return pada Perusahaan Sektor Energi dan Pertambangan Periode 2012-2019 - Habeahan, Edwin; Gandakusuma, Imo (UI Scholars Hub, 2021)
With the increasing awareness of the importance of investment in Indonesian society, particularly in recent years, the number of investors investing in the Indonesian stock market has grown rapidly. This study aims to test whether there is an influence between company performance and company size on stock returns. This research is also to provide a financial assessment to attract investors to develop business in Indonesia, especially in the mining and energy sectors. The sample used is companies en- gaged in the mining and energy sector listed on the Indonesia Stock Exchange from 2012 to 2019 with a sample size of 39 companies. In addition, according to previous research conducted in several other countries, stock returns can be influenced by various factors such as company profitability, company size, risk, dividends, interest rates, supply, demand, inflation, government policies, and the economic situation. From the results of this study, it was found that not all of the tested financial factors had an effect on stock returns, in development classification companies that had a significant effect on stock returns only Earning per Share (EPS) and Market to Book Value Ratio, while other ratios did not significantly affect stock return with a significant level of α = 5%.